2008
DOI: 10.1007/s10637-008-9148-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic activity of tri-n-butyltin(IV)lupinylsulfide hydrogen fumarate (IST-FS 35) and preliminary antitumor activity in vivo

Abstract: The cytotoxicity in vitro and antitumor activity in vivo of the organotin compound tri-n-butyltin(IV)lupinylsulfide hydrogen fumarate (IST-FS 35) have been investigated. The IC50 values obtained in a panel of tumor cell lines were compared to those of the parental compound IST-FS 29 in the same cells. IST-FS 35 resulted significantly more active than IST-FS 29 with IC50 values in the range 0.16-1.8 microM. Toxicity studies in vivo, after intravenous administration of escalating concentrations of IST-FS 35, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The toxic effects of 3a – 3 k were compared with those induced by the analogous pyridoxamine organotin complexes that were orally administered; the results obtained in this study demonstrated that, after acute intraperitoneal administration, pyridoxal complexes 3a – 3 k are more potent than the pyridoxamine organotin complexes described previously, which cause lethality at doses from 200 to 300 mg kg −1 body weight. Moreover, complexes 3a – 3k and 4a – 4c are less toxic than tri‐ n ‐butyltin(IV)lupinylsulfide hydrogen fumarate (LD 50 = 5.40 mg kg −1 ) …”
Section: Resultsmentioning
confidence: 99%
“…The toxic effects of 3a – 3 k were compared with those induced by the analogous pyridoxamine organotin complexes that were orally administered; the results obtained in this study demonstrated that, after acute intraperitoneal administration, pyridoxal complexes 3a – 3 k are more potent than the pyridoxamine organotin complexes described previously, which cause lethality at doses from 200 to 300 mg kg −1 body weight. Moreover, complexes 3a – 3k and 4a – 4c are less toxic than tri‐ n ‐butyltin(IV)lupinylsulfide hydrogen fumarate (LD 50 = 5.40 mg kg −1 ) …”
Section: Resultsmentioning
confidence: 99%
“…Most of the efforts related to anticancer activity have involved the use of monomeric or small molecules [25,26,27,28]. Monomeric organotin compounds have been studied since 1929 as potential anticancer agents.…”
Section: Resultsmentioning
confidence: 99%
“…The tributyltin(IV)-3,4-diaminobenzoate, 3,5-diaminobenzoate and 2- [4-(dimethylamino) phenylazo]benzoate were also found to be promising cytostatic agents in vitro when tested against human cell line A549 (lung adenocarcinoma) [15]. The cytotoxicity of a tributyltin(IV) lupinylsulfide hydrogen fumarate has also been studied and proved to be extremely active when tested in vitro against a panel of tumor cell lines (MCF7, MDA-MB-231 (breast), A2780, OVCAR-3 (ovary), DBTRG-0.5MG, U87 MG, U373 MG, A-172 (glioma) and a mouse glioma cell line (GL261)) and in vivo against P388 (myelomonocytic leukemia) and the B16-F10 (melanoma) cell lines [16].…”
mentioning
confidence: 99%